DESCRIPTIVE ANALYSIS & UML: DIGITAL ARCHIVAL INFORMATION SYSTEM AT THE PROSECUTOR'S OFFICE - Andriasari, Sevi; Ramadaniah, Dedeh; Romahdoni, Muhammad Reza (Asia Information System Journal, 2024)
The increasing importance of digital archival systems in managing legal data efficiently. The methods section describes the use of a descriptive approach and Unified Modeling Language (UML) for system design, emphasizing the systematic analysis of document storage needs at the Central Lampung district attorney's office. Major findings include the inefficiencies of the existing manual archival system, the necessity for a digital archiving solution, and the benefits of UML implementation in improving system efficiency and reliability. The discussion delves into the implications of transitioning to a digital system, such as enhanced accuracy, improved efficiency, and the promotion of collaboration among legal professionals. Suggestions and implications focus on the need for continuous monitoring, staff training, and exploring advanced technologies like artificial intelligence for automated document management. The abstract encapsulates the study's key components, findings, and recommendations, providing a concise yet informative summary of the research on digital archival systems in prosecutorial offices.